پەیوەندى کورد بە بنەماڵەى عەبباسییەکانەوە و ڕۆڵیان لە شۆڕشى عەباسیەکاندا میتۆدێکی مێژوویی - اسماعیل, پ.د.صالح کانەبی; مصطفى, جیهاد نظيف (Sulaimani Journal for Humanities, 2023)
This study is an attempt to shed light on the relationship between the Kurds and the Abbasid dynasty at a certain time period. Based on the sources, the researcher tried to clarify the prelude of the Kurdish relationship with the Abbasid dynasty during the secret campaign and then, on the eve of the Abbasid Revolution which is also known as the Movement of the Men of the Black Raiment, to eradicate the Umayyad dynasty. Here, an attempt has been made by the researcher to unfold the different types and forms of that relation, as well as the direct and indirect presence and cooperation of the Kurds in the revolution .Since most of the conflicts between the Abbasid and the Omayyad took effect in Kurdistan, the Kurds were the right ally of the Abbasids in the triumph of their revolution, and they also backed them in maintaining and merging the foundations of the Abbasid Caliphate.